Beneficial effects of spontaneous fermentation in enhancing the phenolic contents, antioxidant activity and cultivation of lactic acid bacteria of Carica papaya leaf. Issue 1 (December 2020) - So'aib, M S; Hamid, K H K; Salihon, J; Tan, H L; Hamid, A.
Abstract: Spontaneous fermentation using endogenous microorganisms is a reliable method for enhancing the bioactivity of medicinal plant. Here, the method was applied on Carica papaya leaf (CPL) for the first time to enhance the phenolic contents, antioxidant activity, and cultivation lactic acid bacteria. The antioxidant activity was estimated in terms of 2, 2-diphenyl-1-picryl-hydrazyl-hydrate DPPH scavenging activity. Meanwhile, the microorganism fingerprinting was carried out by polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) method. Total phenolic content and antioxidant activity of fermented CPL (day 90) were 45.64±0.69 mg GAE/g dm and 467.38±4.09 mM TE/g dm, respectively, higher than 12.13±0.69 mg GAE/g dm and 275.46±3.09 mM TE/g dm, respectively of control, unfermented CPL. The cultivation of lactic acid bacteria (LAB) was marked by its viable cell counts between 10 3 to 10 7 colony forming unit (CFU)/mL on De Man, Rogosa and Sharpe (MRS) agar medium and the fingerprints of Weisella, Lactobacillus and Lactococcus species on PCR-DGGE throughout the fermentation period.